Chinese Herb Injections in the Adjuvant Treatment for Ulcerative Colitis: A Network Meta-Analysis of Randomized Controlled Trials. (22nd April 2022) - Zhou, Ziyang; Chen, Hao; Shen, Yingkai; Huang, Hailiang
Abstract : Ulcerative colitis refers to an inflammatory disease lasting for a long time, which affects the colon. In China, injections of traditional Chinese herbs have been generally combined with traditional Western medicines such as mesalazine and sulfasalazine to treat ulcerative colitis. Nevertheless, the safety and efficacy exhibited by different CHIs for treating UC remains controversial. Therefore, a network meta-analysis method was employed in this study for the assessment of the effect and safety exhibited by CHI for treating UC. Seven English and Chinese databases were searched for relevant randomized controlled trials (RCTs) from the time of database creation to December 30, 2021. An assessment was conducted for the included RCTs' quality with the use of the Cochrane risk offset assessment device, and this study processed the data with the use of Review Manager 5.3 or Stata16.0 software. On the whole, 42 literature with data on 3668 patients were included. The overall response rate, inflammatory factors, recurrence rate, and adverse reactions were evaluated. In comparison with traditional Western medicines-based treatment, CHI integrated with traditional Western medicines presented an overall response rate (P < 0.05 ) and could better reduce the TNF- α (P < 0.05 ), IL-6(P < 0.05 ), and IL-8 level rate (P < 0.05 ) while better increasing the IL-10 level rate (P < 0.05 ). Besides, adverse reactions of CHI integrated with traditional Western medicine had a lower incidence (P < 0.05 ), and no significant distinction was identified in recurrence rate levels between the two interventions. CHI has some efficacy for treating UC. Xiangdan injection, Shenmai injection, Shengmai injection, and Danshen injection may be the most effective CHI. Nevertheless, more multicenter randomized controlled double-blind trials with great quality and large samples are required for research confirmation. Trial Registration: the registration was made for the protocol of this network meta-analysis in PROSPERO with ID CRD42021251429 .